How to Reduce Radiation Exposure in the Follow-up of Patients with Scoliosis - Hans-Rudolf Weiss; Sarah Seibel (Highlights on Medicine and Medical Research Vol. 11, 2021)
Scoliosis patients are subjected to multiple x-ray investigations during growth. The need for x-rays during regular check-ups when clinical measurements are taken can be reduced (ATR, Surface Topography), however as indications and check-ups still rely on the measurement of the Cobb angle on a full standing x-ray, the exposure of children and adolescents with scoliosis cannot be avoided. Therefore, it would make sense to reduce the exposition of this patient group to radiation drastically. One way to reduce radiation is the reduction of the exposure. The other way is the reduction of the diagnostic field. This study was undertaken to investigate the possibility to use one single 45 x 45 cm detector of a DR system for diagnosing and follow-up of adolescent girls with scoliosis. Materials and Methods: 32 consecutive standing x-rays of girls, aged 10 to 14, made with a single 45 x 45 cm detector of a DR system were analyzed as to whether sufficient information has been provided for diagnosis and follow-up of the patients. Results: Ground plate of Th1 was clearly visible in 31%, ground plate Th2 in 56% and ground plate Th3 in 88% of the rest. Major curvatures (thoracic and lumbar) were fully visible in 100% of those tested. Risser 3 or 4 would have been (or has been) detected in 100% of cases. Conclusion: Adolescent girls with scoliosis can be followed and diagnosed with a drastic reduction of the diagnostic field using a 45 x 45 cm detector of a DR system for direct radiography. A drastic reduction of the exposure to radiation of children and adolescents with scoliosis is easily possible by reducing the diagnostic field (window) and by reducing the exposure time. For proper diagnosis and follow-up, it is rarely necessary to expand the field size to higher than Th3 level.